Acceptance and Commitment Therapy (ACT) for Improving the Quality of Life Patients Suffering Cancer - Krisnana, Ilya; Kusnanto, Kusnanto; Suhardin, Saverinus (Jurnal NERS, 2016)
Introduction: Cancer is a chronic disease that affects physical, psychological, social, and economic life of individual and then contributes to life quality. Psychotherapy is important in improving the life quality of cancer patients. One of psychotherapy that can be given is the implementation of ACT (Acceptance and Commitment Therapy). The aim of this study is to analyze the application of ACT in improving the life quality of cancer patients at the Puskesmas Pacarkeling Surabaya.        Method: This research method used pre-experimental with one group pre-post test design. The population of cancer patients enrolled in the Puskesmas Pacar Keling. Samples were 12 people whom are determined based on the inclusion criteria. The Independent variable is application of ACT and the dependent variable is life quality. Data collection and implementation of ACT were conducted in puskemas and home visits. The collected data was analyzed by Paired T test with significance level α=0.05. Result: Result showed that there was change in increasing life quality of cancer patients significantly after giving implementation of the ACT. The result of Paired t-test showed the life quality of patients had a significance level of p=0.000. These result demonstrate the value of p <0.05, so the research hypothesis is accepted. Discussion: It can be concluded that the application of ACT can improve the life quality of cancer patients. Health workers (nurses) need to master the implementation of the ACT as a therapeutic modality.